Higher Education and Equality of Opportunity: A Review of Findings and Data Sets - Andreou, Sofia N.; Koutsampelas, Christos (My University, 2014)
Amartya Sen (1992), in the prologue of his well appreciated book “Inequality Reexamined,” sets forth the most fundamental question in the study of inequality: “equality of what?” Irrespectively of someone’s ideological predispositions, we can expect that most people will condemn inequality on the grounds of unfairness. Yet, trying to figure out the “proper” concept of inequality is far more elusive.
Keywords: High Education; Human Capital; American Economic Review; Educational Inequality; Intergenerational Mobility